Metaverse Phenomenon in Islamic Perspective: Opportunities and Challenges - Wahyuni; Sadiq, Imam; Ratnah Rahman (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2024)
This paper explores the challenges faced by Muslims in responding to the rise of the metaverse, derived from secondary data sources such as journals and articles. The discussion begins with the background of the growing discourse surrounding the development of the metaverse, particularly driven by technology leaders who aggressively promote this new digital realm. The metaverse refers to an immersive, 3D internet world that is set to revolutionize digital interaction and socialization. As this new virtual space takes shape, it promises to bring significant innovations in communication, education, and business. However, it also raises concerns about the emergence of new forms of immoral behavior, such as addiction, cybercrime, and exploitation, which can affect individuals and societies at large, including the Muslim community. The paper argues that the metaverse's impact on Muslims will be profound, and it is crucial for Muslims to confront these challenges in a way that aligns with Islamic values. By understanding the metaverse’s potential and pitfalls, Muslims can navigate this technological shift wisely, ensuring they harness its benefits while safeguarding their moral and spiritual integrity. The paper suggests that a balanced approach, grounded in Islamic teachings, will enable Muslims to make the best use of the metaverse while minimizing its negative consequences.